THE EFFECT OF SUSTAINABILITY REPORTING ON FIRM VALUE: EVIDENCE FROM IDX-LISTED COMPANIES - Maghfirah (GLOBAL RESEARCH IN ECONOMICS AND ADVANCE THEORY (GREAT), 2025)
This study investigates the effect of sustainability reporting on firm value among companies listed on the Indonesia Stock Exchange (IDX). Employing a mixed-methods approach, it analyzes financial and sustainability data from 100 firms between 2020 and 2023 and supplements it with executive interviews. Firm value was measured using market capitalization, stock performance, and return on equity (ROE), while disclosure quality was assessed through GRI and SASB frameworks. Results show that firms with higher-quality reports achieve stronger financial performance and investor trust, exemplified by PT Astra International Tbk’s 20% stock price increase following its report. Sectoral analysis indicates consumer goods companies lead in proactive sustainability practices, while mining and energy firms face reporting challenges. Overall, sustainability reporting emerges as a strategic tool for accountability, competitiveness, and long-term value creation in emerging markets.